2021
DOI: 10.1111/ina.12902
|View full text |Cite
|
Sign up to set email alerts
|

Acute health effects from exposure to indoor ultrafine particles—A randomized controlled crossover study among young mild asthmatics

Abstract: Particulate matter is linked to adverse health effects, however, little is known about health effects of particles emitted from typical indoor sources. We examined acute health effects of short‐term exposure to emissions from cooking and candles among asthmatics. In a randomized controlled double‐blinded crossover study, 36 young non‐smoking asthmatics attended three exposure sessions lasting 5 h: (a) air mixed with emissions from cooking (fine particle mass concentration): (PM2.5: 96.1 μg/m3), (b) air mixed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 67 publications
(152 reference statements)
1
17
0
Order By: Relevance
“…It is also important to note that residual surface‐bound implant particulate is not continually released in vivo but, as a worst case, can be assumed to be a one‐time bolus dose. Further comparison of exposure level of residual implant particle criteria to everyday exposure (i.e., <1 × 10 7 particles for <1 μm sized residual particles) indicates that it is approximately equivalent to the amount of 0.1 μm sized particles inhaled in 10 average breaths of good quality outdoor air in rural conditions (i.e., 1.3 × 10 6 particles per breath: 0.1 μm particles: 2610 × 10 6 particles/m 3 in good quality rural air, at 500 mL per average breath) 36–38 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to note that residual surface‐bound implant particulate is not continually released in vivo but, as a worst case, can be assumed to be a one‐time bolus dose. Further comparison of exposure level of residual implant particle criteria to everyday exposure (i.e., <1 × 10 7 particles for <1 μm sized residual particles) indicates that it is approximately equivalent to the amount of 0.1 μm sized particles inhaled in 10 average breaths of good quality outdoor air in rural conditions (i.e., 1.3 × 10 6 particles per breath: 0.1 μm particles: 2610 × 10 6 particles/m 3 in good quality rural air, at 500 mL per average breath) 36–38 …”
Section: Discussionmentioning
confidence: 99%
“…that it is approximately equivalent to the amount of 0.1 μm sized particles inhaled in 10 average breaths of good quality outdoor air in rural conditions (i.e., 1.3 Â 10 6 particles per breath: 0.1 μm particles: 2610 Â 10 6 particles/m 3 in good quality rural air, at 500 mL per average breath) [36][37][38]. …”
mentioning
confidence: 99%
“…According to Vicente et al [ 59 ], this increase is especially high during open fireplace operation where PM 10 concentrations can rise up to twelve times as compared to background concentrations. Moreover, candles are very often used during wintertime in Denmark [ 60 ], and a high concentration of candle induced PM 2.5 has shown a mild inflammatory response among young asthmatics as a result of five hours of exposure [ 61 ]. Nevertheless, it has been discussed that addressing ambient and indoor RWC exposure as separate risk factors can lead to double counting due to their interrelated nature [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the published studies on healthy subjects in exposure chambers with candle or cooking emissions, adverse effects on lung function [ 19 ], cardiovascular outcomes including blood pressure, arterial stiffness and heart rate variability [ 20 22 ], and brain activity [ 23 , 24 ] have been demonstrated, though no single effect has been observed in all studies. In a previous publication from the present study, we have reported on changes in the nasal mucosa and exhaled nitric oxide (NO)-concentrations, the particle number and volume size distribution as well as the light scattering ability of the particles, and decreasing self-reported well-being following exposure to cooking and candle emissions among subjects with mild asthma [ 25 ]. In observational and intervention studies, indoor exposure to particles in the fine and ultrafine size range has been associated with systemic inflammatory biomarkers such as declining levels of endothelial progenitor cells, oxidative stress, and release of several cellular mediators, such as cytokines [ 26 29 ], all of above mechanisms relevant in the causal pathway to cardiovascular and pulmonary disease [ 29 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PM properties are discussed in terms of estimated mass distributions and their hygroscopic properties are presented. For the convenience of the reader some description of exposure characteristics already described in [ 25 ] are summarized herein.…”
Section: Introductionmentioning
confidence: 99%